The complete plastome sequence of the endangered orchid Habenaria radiata (Orchidaceae) - Kim, Young-Kee (Mitochondrial DNA B Resour, 2017)
In this study, we determined the complete chloroplast sequence of Habenaria radiata (Thunb.) Spreng. (Orchidaceae) (NCBI acc. no. KX871237), an endangered plant species protected by the national law of Korea. The gene order and gene content of the H. radiata plastome are similar to those of typical angiosperm plastomes. The 11 ndh genes, which are usually lost in orchid plastomes, are intact in the H. radiata plastome. The complete plastome is 155,353 bp in length and consists of a large single copy of 84,833 bp and a small single copy of 17,718 bp, separated by two inverted repeats of 26,401 bp. The plastome contains 113 genes, of which 79 are protein-coding genes, 30 are tRNA genes, and four are rRNA genes. Sixteen genes contain one intron and two genes (clpP, ycf3) have two introns. A total of 76 simple sequence repeat (SSR) loci, which consist of 58 mono-SSR, 17 di-SSR, and 1 tri-SSR, are scattered along the H. radiata plastome. Some of these plastome SSR and high sequence divergent regions may be useful for development of genetic markers for the populations of H. radiata and other congeneric species. Phylogenetic analysis identified the sister relationship between H. radiata and H. pantlingiana within the tribe Orchideae.